2016
DOI: 10.1055/s-0042-111011
|View full text |Cite
|
Sign up to set email alerts
|

A Retrospective Perinatal Data Analysis of Immigrant and German Women from Representative Birth Cohorts at the Virchow Hospital, Berlin

Abstract: Introduction: The aim of this study was to define and characterise differences in the level of obstetric care provided to immigrant and German women. Materials and Methods: An analysis of the Virchow Hospital?s birth registers was conducted for the years 1974, 1984 and 1994. The study population of 5445 patients was grouped according to ancestry/family origin on the basis of a name analysis, and subsequently also according to parity (primiparous or multiparous). On name analysis 2741 women were defined as Ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…Finally, further research could also establish whether the association between income and obstetric care holds when looking at other perinatal outcomes such as episiotomy, use of uterine stimulants, analgesics in labor and anesthesia in migrant populations. Indeed, two studies conducted in Berlin [19,27] and one in the Netherlands [28] found differences in anesthesia provision and induction of labor between women with and without migration backgrounds. While two of them included measures of socioeconomic position (education [19,28] and neighborhood socioeconomic status [28]) none took into account the individual or household income of participants.…”
Section: Implications Of the Resultsmentioning
confidence: 99%
“…Finally, further research could also establish whether the association between income and obstetric care holds when looking at other perinatal outcomes such as episiotomy, use of uterine stimulants, analgesics in labor and anesthesia in migrant populations. Indeed, two studies conducted in Berlin [19,27] and one in the Netherlands [28] found differences in anesthesia provision and induction of labor between women with and without migration backgrounds. While two of them included measures of socioeconomic position (education [19,28] and neighborhood socioeconomic status [28]) none took into account the individual or household income of participants.…”
Section: Implications Of the Resultsmentioning
confidence: 99%
“…Whether this heterogeneity is related to differences in definitions and methods of measuring migration and maternal outcomes or to real differences between settings remains unclear. Studies have defined migrant women according to their race or ethnicity [18][19][20][21][22][23], nationality [24][25][26][27], or their birthplace [14,16,17,[28][29][30][31][32][33]. A few others have used other criteria, such as the Human Development Index of the country of origin [34], length of residency in the host country, or legal status [35].…”
Section: Introductionmentioning
confidence: 99%